Integrating ‘common good’ authenticity for sustainable human resource management reporting - Järlström, Maria; Saru, Essi; Viitasaari, Maija; Akrivou, Kleio (Sage, 2024)
This study draws on arguments from common good theory to explore the sustainable human resource management (S-HRM) reporting. Specifically, the purpose of the study is to determine how to improve the common good authenticity of sustainability reporting in HRM. Our qualitative data consist of sustainability reports from the 40 most sustainable corporations from the Global 100 index. In the reporting data, we identified four HRM themes, and several aligned HRM practices, with measures that support common good values. Our research strengthens the connection between the common good values and CGHRM by comprehensively defining and explaining the common good values. By doing so, we emphasise the need for a humanistic-ethical orientation expressed by treating employees with respect and dignity. We also identify areas in which current reporting falls short, including the outside-in perspective of CGHRM.
Keywords: Common good HRM; common good values; sustainability reports; sustainable HRM practices; sustainable HRM; fi=Henkilöstöjohtaminen|en=Human Resource Management|